Freezing capacity of sperm on various type of superior bulls - Eros Sukmawati; R. I. Arifiantini; B. Purwantara (Indonesian Center for Animal Research and Development (ICARD), 2014)
Low quality of sperm after freezing and thawing process due to changes in extreme temperature and osmolarity. The sperm freezing capability and sperm membrane damage was to evaluate by measuring the levels of malondialdehyde (MDA) of Simmental, Limousin and Friesian Holstein (FH) bull of a total of 10 bulls aged 4-8 years. Data were analyzed with a linear model (GLM) and Duncan 's test. Results showed that breed influence sperm motility and MDA levels but not in the membrane integrity (MI) and viability. The FH bull had a low of recovery rate (RR) 57.53± 1.74% with high MDA level (0.81± 0.31 nmol/108 sperm level) and Limousine had the highest RR (59.70 ± 3.23% ) with the low MDA (0.52±0.25 nmol/108 sperm). Freezing decreased the sperm motility, viability and MI of all bulls. Sperm motility, viability and MI decreased by 28.32±1,45% and 29.73±1.54%, 21.58±4.09% and 22.55± 5.60% and 21.25±6.86% and 23.51±6.05 % respectively.